2016
DOI: 10.1177/1748895816654530
|View full text |Cite
|
Sign up to set email alerts
|

Restoring identity: The use of religion as a mechanism to transition between an identity of sexual offending to a non-offending identity

Abstract: Kewley, S, Larkin, M, Harkins, L and Beech, ARRestoring identity: The use of religion as a mechanism to transition between an identity of sexual offending to a non-offending identity http://researchonline.ljmu.ac.uk/7028/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Similarly, comparatively few desistance studies attend to desistance from sex offending; of those that do, the focus is overwhelmingly on people convicted of sex offending against children (e.g. Hulley, 2016;Kewley 2016;McAlinden et al, 2016). As such, diversities within and across crime types remain undeveloped.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Similarly, comparatively few desistance studies attend to desistance from sex offending; of those that do, the focus is overwhelmingly on people convicted of sex offending against children (e.g. Hulley, 2016;Kewley 2016;McAlinden et al, 2016). As such, diversities within and across crime types remain undeveloped.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Kruttschnitt et al (2000), for example, in their large-scale study of 556 individuals convicted of sexual offences found that job stability significantly reduced the probability of reoffending, but that marital status had no significant effect on desistance (see also Schaeffer et al, 2004;Van den Berg et al, 2014). Although the authors did not explore more subjective or cognitive changes associated with desistance, Harris' (2014) qualitative investigation of desistance among a group of 21 adult males convicted of sexual offences identified a continuum of cognitive transformations, ranging from a simple recognition that the individual has caused harm through to the creation of a new, non-offending identity (see also Farmer et al, 2012;Kewley et al, 2016).…”
Section: Desistance From Sexual Crimementioning
confidence: 99%
“…Most of this work has been either theoretical (McAlinden, 2007;Laws and Ward, 2011) or else exploratory in nature with small sample sizes (e.g. Farmer et al, 2012;Kewley et al, 2016), but a portrait of how desistance works for this population is starting to emerge. Kruttschnitt et al (2000), for example, in their large-scale study of 556 individuals convicted of sexual offences found that job stability significantly reduced the probability of reoffending, but that marital status had no significant effect on desistance (see also Schaeffer et al, 2004;Van den Berg et al, 2014).…”
Section: Desistance From Sexual Crimementioning
confidence: 99%
“…There has been a plethora of research examining the putative impact of religion on desistance from offending, seeking to explain how religion may inhibit an individual from continuing to commit crime (Hallett and McCoy 2015;Salas-Wright et al 2016;Eshuys and Smallbone 2006;Kewley et al (2015Kewley et al ( , 2016). As a mainstream religion in Western society, Christianity is typically the religion that is the focus for this type of research.…”
Section: Introductionmentioning
confidence: 99%
“…For these individuals, nasty societal attitudes to "sex offenders" will be just one of the challenges they face on release from prison. Kewley et al (2016) highlighted how religious prisoners could find that the process of reintegrating with society is helped by their engagement with a religious group or community, yet the authors state: "However, some caution is needed as the transition from offender to non-offender was not seamless or straightforward for those with an innate sexual interest in children" (p. 21). This is one element that distinguishes sexual offenses from other types of offenses, as sexual interest can be difficult or sometimes impossible to change (Beckstead 2012).…”
Section: Introductionmentioning
confidence: 99%